2016
DOI: 10.5430/jct.v5n1p11
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Lecture Capture and Student Performance in Physiology

Abstract: Lecture capture technology is fairly new and has gained interest among higher institutions, faculty and students alike. Live-lecture (LL) is captured in real-time and this recording, LC, is made available for students to access for later use, whether it be for review purpose or to replace a missed class. Student performance was compared between those attending LL only and the other group utilizing LC in addition to LL in two randomly chosen lectures. We found that the overall exam performance was indistinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…At the second measuring point, there was a relative reduction in the perception of a contribution by the ClassBoost system to learning from the student teachers' viewpoint. This aspect is in line with the findings of previous research, which found that use of LCT was not expressed in alterations in the learners' achievements (Bollmeier et al, ; Drouin, ; Hadgu, Huynh, & Gopalan, ; Pale et al, ). We estimate that the reduction in the perception of the contribution of the ClassBoost system to learning is also connected to the fact that not all the qualities of the ClassBoost system were exploited, and the students did not know about or were not exposed to all the means and possibilities of this system.…”
Section: Discussionsupporting
confidence: 92%
“…At the second measuring point, there was a relative reduction in the perception of a contribution by the ClassBoost system to learning from the student teachers' viewpoint. This aspect is in line with the findings of previous research, which found that use of LCT was not expressed in alterations in the learners' achievements (Bollmeier et al, ; Drouin, ; Hadgu, Huynh, & Gopalan, ; Pale et al, ). We estimate that the reduction in the perception of the contribution of the ClassBoost system to learning is also connected to the fact that not all the qualities of the ClassBoost system were exploited, and the students did not know about or were not exposed to all the means and possibilities of this system.…”
Section: Discussionsupporting
confidence: 92%
“…Other research indicates that students believe lecture capture improves their performance because they are able to review difficult sections and revisit the material as often as needed (Al-Nashash and Gunn 2013; Groen et al 2016). However, studies using actual grades show a mixed picture, with some indicating a positive relationship between lecture capture availability/use and actual grades (Bollmeier et al 2010;Francom et al 2011; Wiese and Newton 2013;Yu et al 2015) and others reporting little or no relationship between the two (Abt and Barry 2007;Brotherton and Abowd 2004;Edwards and Clinton 2018;Hadgu et al 2016). Despite this mixed picture on performance, availability of lecture capture increases student satisfaction (Al-Nashash and Gunn 2013; Brecht and Ogilby 2008;Bryans Bongey et al 2006;Greenberg and Nilssen 2009;Secker et al 2010;Toppin 2011;Traphagan et al 2010;Veeramani and Bradley 2008;Woo et al 2008) and affects course choice such that modules with lecture capture are more likely to be selected (Vajoczki et al 2011;Watt et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Aldamen et al (2015) state that a slight positive relationship was observed between captured lecture viewership and performance in their class. However, others state that there is essentially no difference between video users and non-users (Bosshardt and Chiang, 2016;Hadgu et al, 2016;Williams et al, 2016). Day and Foley (2006) attempted to quantify the benefit of lecture capture material by dividing a class into two groups, a group who attended lectures as normal and a group who were offered access to lecture recordings.…”
Section: Exam Resultsmentioning
confidence: 99%